(untitled) (Innovaciones Educativas, 2025)
This research had as objective to analyze the feasibility of the connection between technologies based on Internet of Things (IoT) with the mediation of environmental education practices that contribute to improve scientific competencies, technological abilities, and environmental awareness in formal education contexts. A systematic literature review from papers and thesis published in the last 12 years was developed. This process had three stages: 1) identification, 2) screening, and 3) inclusion of the selected studies. Databases such as IEEE Xplore, Science Direct and Scielo were consulted, as well as the search engine Scholar Google. From the inclusion and exclusion process, were selected a total of 35 publications: 30 papers, two books and three theses. The research results are organized in four subjects: 1) IoT integration in environmental education experimental practices, 2) instrumentation of IoT devices, 3) programming software and tools, and 4) methodological design of environmental education experimental practices. It was shown that the implementation of low-cost educational hardware based on IoT offers the possibility of developing educational experiences which allow students to obtain environmental knowledge through monitoring physical parameters contextualized to formal learning environments. Besides, it was determined that technologies emerged from the 4.0 Industry represent an opportunity to impulse educative innovation in science teaching. The main limitations identified include the availability of research about IoT integration in environmental education, and the methodological diversity among the analyzed studies.